Technological Transformation for the Collection of Zakat, Tax and Custom in Saudi Arabia - Omar Ibrahim Alzaidan (MultiTech Publisher, 2024)
The technological transformation of revenue collection processes, encompassing Zakat, tax, and customs administration, has emerged as a significant initiative in Saudi Arabia's pursuit of modernization and efficiency in fiscal governance. This paper explores the implications and insights derived from this transformation, shedding light on the advantages, challenges, and future prospects associated with the integration of technology in revenue administration. Through a comprehensive review of literature, government documents, and expert insights, the paper examines how technological advancements enhance accuracy, efficiency, compliance, transparency, cost savings, and resource allocation in revenue collection. Furthermore, it analyzes the impact of technology on various stakeholders, including taxpayers, government agencies, businesses, and the economy as a whole. While acknowledging the challenges of initial implementation costs, resistance to change, cybersecurity risks, and disparities in digital literacy, the paper underscores the transformative potential of technology in driving sustainable growth and development. Recommendations are provided for policymakers and stakeholders to effectively leverage technology while mitigating challenges, emphasizing the importance of continued innovation, collaboration, and investment in technological infrastructure.